Analisis Konsentrasi Belajar Siswa Terhadap Hasil Penilaian Akhir Semester - Beni Setiawan; Ahmad Supendi; Hilaria Fitri (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
Researchers analyzed the effect of concentration on learning through this study. The available evidence indicates that a large number of students experience a lack of concentration when studying mathematics. Consequently, they are unable to have a constructive disagreement. Descriptive qualitative research approach is the type of analysis used. The subject of this research is a class consisting of 23 students of class XI. The method used in this study is a qualitative descriptive method using data collection tools in the form of questionnaires, observations, and interviews. The results showed that the percentage of students who took part in class XI Mathematics at SMK Nusantara Indah was included in the category of being able to understand when the teacher explained in class with an average score of 60%. . Class calm and the method used during the process are two factors that influence students' learning interest.